Optimalisasi Proses Pergantian Punch pada Mesin Bending dengan Metode Single Minute Exchange of Dies - Wahyudi, Muzaki; Setiawan, Indra (Jurnal Optimalisasi, 2025)
This research was conducted at a heavy equipment manufacturing company located in the West Java. The researcher was placed as an intern in the Production Engineering department, responsible for designing, managing, and improving production processes to ensure smoothness, efficiency, and quality in production. The study aimed to enhance the efficiency of the punch changeover process on the bending machine in the material preparation area using the Single Minute Exchange of Dies (SMED) method. The main issue identified was that the addition of new machines in the cutting process necessitated a faster forming process. By applying SMED, this research focused on reducing punch changeover time. The research method involved analyzing the punch changeover process on the YSD bending machine, implementing the separation of internal and external activities, and designing a custom trolly to facilitate the transportation and arrangement of equipment. The results showed that the application of SMED successfully reduced punch changeover time by 1.12%, from 1780 seconds to 1760 seconds. Additionally, with the introduction of a custom trolly, the efficiency of punch changeover further increased, resulting in a total reduction in punch changeover time of 38.31%, from 1780 seconds to 1098 seconds. This underscores the importance of combining various process improvement methods to achieve optimal results in enhancing production efficiency